Organizational and Economic Basis of Natural and Man-Made Disasters Consequences Management - TELIZHENKO, Olexandr; MASHYNA, Yuliia; OPANASYUK, Yuliia (Journal of Environmental Management and Tourism, 2017)
The article considers economic essence and factors of natural and man-made disasters economic consequences. Theoretical and methodological principles of organizational and economic mechanism of disasters consequences management are developed. Scientific and methodological approach to the assessment of ecological and economic damages from natural and man-made disasters by rapid method is presented. Reserve fund means distribution mechanism of State budget of Ukraine for prevention and compensation of natural disasters consequences on the basis of region economic potential decrease is developed. The mechanism of branch compensation funds formation is offered, taking into account the probabilistic nature of disasters occurrence on the basis of specific damages indices system, which permits to minimize budgetary expenditures for disasters prevention and elimination.